DAMPAK TARIF PAJAK PENGHASILAN TERHADAP MOTIVASI PENINGKATAN JABATAN AKADEMIK DOSEN DI INDONESIA - Serly Novianti; Faizah Kamilah (Jurnal Akuntansi Kompetif, 2026)
Improving the academic position of lecturers is a strategic aspect in career development and improving the quality of higher education in Indonesia. Based on data from the Higher Education Database (PDDikti) of the Ministry of Education and Culture in 2024, there are 303,067 active lecturers in Indonesia, but the proportion of lecturers with the positions of Head Lecturer and Professor is still below 20%. One of the factors that has been proven to affect the low motivation for promotion is the Income Tax (PPh) rate which is considered not comparable to the additional income received after promotion. This study quantitatively and descriptively aims to prove the significant influence of income tax rates on the motivation to increase the academic position of lecturers in Indonesia. Data was collected through an online survey of 312 lecturers from various public and private universities in Indonesia, which were selected by purposive sampling. The analysis is carried out by simple linear regression using the help of statistical software. The results of the study showed that the income tax rate had a negative and significant effect on the motivation to increase the academic position of lecturers (regression coefficient = -0.342; significance value 0.000 < 0.05). This means that the higher the tax rate imposed, the lower the motivation of lecturers to improve academic positions. This study empirically confirms that a disproportionate tax rate policy has the potential to reduce the academic productivity of lecturers. Therefore, a fairer and performance-based fiscal policy is needed to encourage the improvement of academic positions and strengthen the performance of the tridharma of higher education in Indonesia.